Patient-reported outcomes and complications of a new-generation total knee system: a randomized controlled trial - Kristian R L Mortensen; Lina H Ingelsrud; Anders Odgaard; Andreas Kappel; Claus Varnum; Henrik Schrøder; Kirill Gromov; Anders Troelsen (Acta Orthopaedica)
Background and purpose: Documentation of new-generation implants’ short-term performance could reassure surgeons and patients about their use, while awaiting the long-term outcome. Our aim was to compare the performance of a newer total knee arthroplasty (TKA) system with its predecessor, measured by patient-reported knee function, pain, and complication rate. Methods: We performed a multi-center, randomized, controlled trial (clinicaltrials.gov ID: NCT03073941). 314 patients with primary osteoarthritis were randomized to treatment with a Persona or NexGen cruciate-retaining TKA system and followed for 2 years. The primary outcome was measured with the patient-reported outcome (PRO) Oxford Knee Score (OKS) 2 years post-surgery. Secondary outcomes were the OKS-Activity and Participation questionnaire (OKS-APQ), Forgotten Joint Score (FJS), EQ-5D-3L, and number of complications during the study period. Responder analyses were performed using Patient Acceptable Symptom State (PASS) and Minimal Important Change (MIC) criteria. Results: Primary outcome was available from 289 patients (92%). We found no difference in adjusted mean OKS between the groups 2 years post-surgery (0.1, 95% confidence interval –1.4 to 1.7). We found no significant differences in adjusted mean of secondary PROs, PRO time-weighted averages, proportion of patients with PASS or MIC, or complications 2 years post-surgery. Conclusion: We found no difference in OKS 2 years post-surgery, or in any secondary variables analyzed including complications, between the 2 TKA systems. Short-term safety and performance of the Persona TKA was comparable to its predecessor